Selection of universal peptide biomarkers for the detection of the allergen hazelnut in food trough a comprehensive, high resolution mass spectrometric (HRMS) based approach. (30th March 2020) - Van Vlierberghe, Kaatje; Gavage, Maxime; Dieu, Marc; Renard, Patsy; Arnould, Thierry; Gillard, Nathalie; Coudijzer, Katleen; De Loose, Marc; Gevaert, Kris; Van Poucke, Christof
Highlights: HRMS forms a promising tool for detection of the allergen hazelnut in food. Selection of suitable peptide biomarkers is hereby crucial. Specificity, robustness, peptide composition and intensity are selection criteria. 8 peptides were identified as suitable biomarkers for detection of hazelnut in food. Abstract: The interest of using LC-MS/MS as a method for detection of allergens in food is growing. In such methods, peptides are used as biomarkers for the detection and quantification of the allergens. The selection of good biomarker peptides is of high importance to develop a specific, universal and sensitive method. Biomarkers should, for example, be robust to food processing. To evaluate robustness, test material incurred with hazelnut having undergone different food processing techniques was produced. Proteins of these materials were extracted, digested and further analyzed using HRMS. After peptide identification, selection was carried out using several criteria such as hazelnut specificity and amino acid composition. Further selection was done by comparing peptide MS intensities in the different food matrices. Only peptides showing processing robustness were retained. Eventually, eight peptides coming from three major hazelnut proteins were selected as the best biomarkers for hazelnut detection in processed foods.